Transnationalisation of Telenovelas: How Women in Accra Shape their Local Identities in Response to Aspects of the Latin American Version of Soap Operas - Ahiabor, Gabriel Kodjo (UniMAC-GIJ, 2015)
Soap operas have come to stay with the Ghanaian media, especially, television stations. It is for this reason that proper attention needs to be given as far as airing these programmes are concerned. This study was generally aimed at investigatinghow transnationalisation of telenovelas is eroding the fibres of the Ghanaian culture. Specifically, it sought to find out the extent of attention given to soap operas by the Ghanaian media, televisions in this regard, examined the impact of these operas on the Ghanaian culture and ascertained the transnationalisation dimension of the operas and globalisation and commercialisation on the item oftmth. The probability sampling method was used in obtaining the required data from the 250 respondents, with majority being females whose ages ranged between 18 and 60 years. The data were subsequently analysed using the numeric tables, graphs and charts. The findings from the study have revealed that the media was contributing largely to the general destmction of the Ghanaian cultme. It was also realised that the media was giving too much attention to the broadcasting of soap operas across the country, with less attention given to the local movies. In view of the fact that the media had recognised that women were large consumers of soap operas, they would continuously televise the programme to meet their demands. This, to all intents and purposes has gone a long way to increase the commercialisation aspect of telenovelas since such programmes attract a lot of advel1isements from large companies and institutions. Consequently, it was revealed that women were losing touch with their Ghanaian culture.
MA Journalism